2019
DOI: 10.3390/su11164256
|View full text |Cite
|
Sign up to set email alerts
|

Motivation, Anxiety, and Emotional Intelligence Are Associated with the Practice of Contact and Non-Contact Sports: An Explanatory Model

Abstract: (1) Background: Several studies have shown that high anxiety impairs sport performance, making it important to develop strategies which improve the emotional self-regulation of athletes. The present study analyzed the relationship between emotional intelligence, motivational climate in sport, and anxiety according to participation in contact or non-contact sports, using multi-group structural equation modeling; (2) Methods: This research was conducted with a sample of 371 semi-professional athletes from Spain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 63 publications
3
17
0
2
Order By: Relevance
“…The same situation is found for the self-concept of athletes; we found a direct and positive relationship between self-concept and the levels of emotional intelligence [ 10 ]. As with motivation, studies showed that high levels of emotional intelligence have a continuous and existing correlation with self-concept [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The same situation is found for the self-concept of athletes; we found a direct and positive relationship between self-concept and the levels of emotional intelligence [ 10 ]. As with motivation, studies showed that high levels of emotional intelligence have a continuous and existing correlation with self-concept [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…This wealth has allowed it to be treated as a multidimensional concept to be not limited or adjusted to a given plane. For instance, Castro-Sánchez et al [1] report that motivation is one of the most studied variables because it explains human behavior. In the context of recreational and professional physical activity, it provides an understanding of factors such as the choice of a sports modality, the persistence, performance, and intensity of a specific sports activity.…”
Section: Motivation Associated With Sports Environmentsmentioning
confidence: 99%
“…Of the motivation theories that stand out in sport psychology for their emphasis on social factors are the self-determination theory developed by Deci and Ryan in 1985 and the achievement goals theory formulated by Nicholls in 1989. These Proposals explain the training and competition situations towards success [1].…”
Section: Motivation Associated With Sports Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…D'ailleurs, la résilience est un concept clé associé à une diminution de l'anxiété de performance, et ce en particulier dans le domaine sportif (Sarkar et Fletcher, 2014). De plus, un athlète intelligent émotionnellement a moins tendance à être anxieux face à la réalisation d'une performance (Castro-Sánchez et al, 2019). Ces athlètes sont alors en mesure d'identifier leurs émotions, de s'autoréguler et de bien gérer leurs relations avec autrui (Laborde et al, 2018).…”
Section: Facteur De Risque Et De Protection Personnelsunclassified